Mechanistic insights of desmopressin loaded elastic liposomes for transdermal delivery: HSPiP predictive parameters and instrumental based evidences - Afzal Hussain; Mohammad A. Altamimi; Musaad A. Alshammari (Elsevier, 2024)
Desmopressin acetate (DA) is a first-line option for the treatment of hemophilia A, von Willebrand's disease, nocturnal enuresis, central diabetes insipidus, and various traumatic injuries. We extended previously reported desmopressin-loaded elastic liposomes (ODEL1) to investigate mechanistic insights into ODEL1 mediated augmented permeation across rat skin. HSPiP software and instrumental techniques such as differential scanning calorimeter (DSC), Fourier Transform infrared (FTIR), scanning electron microscopy (SEM), and fluorescent microscopy provided better understandings of permeation behavior. HSPiP was used to compare Hansen solubility parameter (HSP) of ODEL1, DA, components, and rat skins (control and treated) in terms of dispersion forces (δd), polar forces (δp), and hydrogen bonding (δh). FTIR, DSC, fluorescence microscopy, and SEM provided a detailed mechanistic understanding of the changes occurred after treatment. The values of δd, δp, and δH for DA were 20.6, 31.9, and 18.2 MPa1/2, respectively, whereas these were 15.6, 14.97, and 2.4 MPa1/2 for ODEL1, respectively, suggesting remarkable permeation of DA by changing innate cohesive energies of the skin. DA primarily interacts through δd and δp with the ODEL1 and the skin. Furthermore, the stretching and bending vibrations (molecular interactions) of the treated skins were quite diverse as compared to the untreated skin. ODEL1 caused a substantial thermal changes (shifted 67 to 65 °C, and 79 to 82.5 °C) for the surface protein and glycoprotein as compared to the untreated skin. Fluorescence and SEM confirmed relatively intense surface perturbation of the treated skin as compared to the control. Thus, ODEL1 was efficient in interacting with the skin surface for reversible changes and subsequently resulted in high permeation and drug deposition.